2013
DOI: 10.1093/nar/gkt297
|View full text |Cite
|
Sign up to set email alerts
|

Insulator protein Su(Hw) recruits SAGA and Brahma complexes and constitutes part of Origin Recognition Complex-binding sites in the Drosophila genome

Abstract: Despite increasing data on the properties of replication origins, molecular mechanisms underlying origin recognition complex (ORC) positioning in the genome are still poorly understood. The Su(Hw) protein accounts for the activity of best-studied Drosophila insulators. Here, we show that Su(Hw) recruits the histone acetyltransferase complex SAGA and chromatin remodeler Brahma to Su(Hw)-dependent insulators, which gives rise to regions with low nucleosome density and creates conditions for ORC binding. Depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 63 publications
2
45
0
5
Order By: Relevance
“…Moreover, Gcn5 co-occurs with CP190 at CP190 standalone sites (Figure 3). Previously, the occurrence of SAGA components ENY2, Ada2b or of Gcn5 has been detected at selected dCTCF or Su(Hw) sites (20,52,53), which now may be explained in part due to CP190 binding at these sites in addition to direct contacts with dCTCF or Su(Hw). Nucleic Acids Research, 2017, Vol.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Gcn5 co-occurs with CP190 at CP190 standalone sites (Figure 3). Previously, the occurrence of SAGA components ENY2, Ada2b or of Gcn5 has been detected at selected dCTCF or Su(Hw) sites (20,52,53), which now may be explained in part due to CP190 binding at these sites in addition to direct contacts with dCTCF or Su(Hw). Nucleic Acids Research, 2017, Vol.…”
Section: Discussionmentioning
confidence: 97%
“…In support of this hypothesis, G-rich elements were identified as a binding site for ORC in mouse rDNA (Zellner et al 2007), and a recent biochemical analysis showed that purified ORC could bind to G4 RNA or DNA (Hoshina et al 2013). In the Drosophila genome, ORC binding sites contain a central GC-rich region surrounded by AT-rich sequences (Vorobyeva et al 2013). G-rich motifs/G4 may help in destabilizing the proximal double-stranded DNA structure (König et al 2013), facilitating the MCM2-7 helicase access to the leading single-stranded DNA template.…”
Section: G-rich or G4 Signatures At Replication Origins And Nucleosommentioning
confidence: 99%
“…It is likely, that in the heterochromatin, ORC also binds to the islands of ‘locally open’ chromatin. For example, in the heterochromatin of Drosophila , ORC binds predominantly to the insulators of the Su(Hw) type [95]. …”
Section: Replication Timingmentioning
confidence: 99%